2020
DOI: 10.1108/jpbm-06-2019-2442
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness, trustworthiness and expertise – social influencers’ winning formula?

Abstract: Purpose The importance of influencer marketing is constantly growing. However, little empirical research has examined influencers’ success requirements. This study aims to fill this gap by exploring whether the requirements of influencers’ attractiveness, expertise and trustworthiness are relevant for online influencer campaigns. An entry-level luxury fashion brand is the focus of the experiment. Design/methodology/approach A total of 288 participants completed an online survey evaluating the profiles of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
175
1
31

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 221 publications
(214 citation statements)
references
References 113 publications
7
175
1
31
Order By: Relevance
“…However, to explore the process from a different perspective, it would be worthwhile to also record the opinions of influencers and practitioners on congruence issues. Wiedmann and von Mettenheim (2020) indicated that the perceptions of consumers, influencers and practitioners on the success factors of an endorsement might vary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to explore the process from a different perspective, it would be worthwhile to also record the opinions of influencers and practitioners on congruence issues. Wiedmann and von Mettenheim (2020) indicated that the perceptions of consumers, influencers and practitioners on the success factors of an endorsement might vary.…”
Section: Discussionmentioning
confidence: 99%
“…As influencer marketing has become more popular in recent years, scholars have investigated its success factors. Wiedmann and von Mettenheim (2018, 2020) presented an overview of the success factors of endorsers and influencers in particular and suggested five main categories of success factors: (a) endorser distinctive factors, which describe factors that are inherent to the endorser (e.g., attractiveness, trustworthiness); (b) perceiver congruence factors, which involve the interplay of the endorser with a targeted audience; (c) brand/product congruence factors, which describe the interplay of the endorser with the brand; (d) management factors, which include “behind‐the‐scenes” administrative issues such as the financial constraints of the endorsement and, finally, (e) communication factors, which are related to the issue of whether an endorser can communicate in an adequate way, for example, the suitability of his or her voice. Given the goals of the current work, the literature review will focus especially on literature addressing the categories of (a) perceiver congruence factors and (b) brand/product congruence factors.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…They express their opinions, offer tips on product usage and post pictures, videos or stories of products and services on their social media accounts, giving the impression that this content comes from "a person like you or me"-a non-cunning consumer [1].…”
Section: Introductionmentioning
confidence: 99%
“…SMIs are most commonly used in the fashion industry for endorsement [1]. Fashionistas such as Chiara Ferragni play prominent roles in the fashion industry, introducing branded designs to their followers by posting photos of themselves wearing the designs on their social media accounts [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation